2016
DOI: 10.21314/j0r.2016.332
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the performance of the skewed distributions to forecast value-at-risk in the global financial crisis

Abstract: Executive summary:This paper evaluates the performance of several skewed and symmetric distributions in modeling the tail behavior of daily returns and forecasting Value at Risk (VaR). First, we used

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 36 publications
1
2
0
Order By: Relevance
“…Hajihasani et al (2021) demonstrated the superior performance of q-Gaussian distribution VaR models over traditional normality-based VaR models. In line with this, Abad et al (2016) found that skewed distribution models outperform both normal and Student T distributions during financial distress. Miletic and Miletic (2015) further corroborated the superiority of GARCH-type VaR models over traditional variants.…”
Section: Value-at-risk Concepts and Limitationssupporting
confidence: 67%
“…Hajihasani et al (2021) demonstrated the superior performance of q-Gaussian distribution VaR models over traditional normality-based VaR models. In line with this, Abad et al (2016) found that skewed distribution models outperform both normal and Student T distributions during financial distress. Miletic and Miletic (2015) further corroborated the superiority of GARCH-type VaR models over traditional variants.…”
Section: Value-at-risk Concepts and Limitationssupporting
confidence: 67%
“…We use M1 and M2 as a general notation to refer to any pair of models under comparison. 2 Definition 1. Let β be some specified threshold between 0 and 1, let R 1 and R 2 be the number of VaR validation tests in which the models M1 and M2 are rejected at a chosen significance level p, and let r 12 be the number of common rejections for both models.…”
Section: Dominance Among Var Modelsmentioning
confidence: 99%
“…A key limitation of such tests is that they do not distinguish between returns that are below but far from the VaR and those that are below but close to the VaR. A standard solution has consisted in considering some loss function defined on excess returns over and above the VaR (see, for example, Abad et al, 2016;;Gerlach et al, 2011; Lee and Su, 2015;Louzis et al, 2014;Ozun et al, 2010). Various heuristic criteria have been proposed in the literature to support specific loss functions, usually penalizing models that produce exceedances with a large deviation from VaR (see, for example, Lopez, 1998Lopez, , 1999Sarma et al, 2003; Giacomini and Komunjer, 2005;Caporin, 2008).…”
Section: Introductionmentioning
confidence: 99%